HUBUNGAN TINGKAT PENGETAHUAN TENTANG MENSTRUASI DENGAN KESIAPAN MENGHADAPI MENARCHE PADA SISWI KELAS V DAN VI DI SD NEGERI DANGKEL PARAKAN TEMANGGUNG TAHUN 2014 - Anisatun Afifah; Tulus Puji Hastuti (JURNAL KEBIDANAN, 2016)
Adolescence or puberty is a period in which the human body is undergoing changes that include growth and development. The most important events in puberty girls are the symptoms of menstruation or menstrual be a biomarker of sexual maturity. Knowledge and a good attitude about the physical and psychological changes associated menarche indispensable. Young women will have difficulty in dealing with menarche if not previously been aware of or discuss either with peers or with their mother.        The purpose of this study was to determine the relationship of the level of knowledge about menstruation with preparedness menarche in grade V and VI in Dangkel Parakan Waterford Elementary School. Respondents in this study consisted of 34 respondents who have not experienced menarche. The scale used in this study are nominal and ordinal scale statistical test used is the Kolmogorov-SmirnovFrom the results of the 34 respondents, good knowledge of students who were 21 (61.8%) have been prepared for menarche. Respondents with sufficient knowledge and are ready to face menarche 4 (11.8%). This study used a statistical test of Kolmogorov-spirnov with the result p value = 0.015 (p 0.05), so that Ho is rejected Ha accepted, meaning that there is a correlation with the level of knowledge about menstruation menarche preparedness.The suggestions in this study were more active for health centers to provide health education on reproductive health to elementary school student who was working in the region.